Business analysis and valuation : using financial statements : text and cases - Palepu, Krishna G.; Bernard, Victor L.; Healy, Paul M. (Cincinnati, OH : South-Western College, 2000)
This book is about: Framework; Business analysis and valuation tools; Business analysis and valuation applications; Additional cases; ...
Keywords: Finance; Business enterprises; Business enterprises -- Valuation; Financial statements; Business enterprises -- Valuation -- Case studies